2017
DOI: 10.14507/epaa.25.2636
|View full text |Cite
|
Sign up to set email alerts
|

School choice or the politics of desperation? Black and Latinx parents of students with dis/abilities selecting charter schools in Chicago

Abstract: Abstract:In this paper, we focus on the city of Chicago to examine how Black and Latinx parents of students with dis/abilities 1 engage with school choice. Using analytical tools from 1 We used the term dis/ability with a slash "to denote dis/ability not as an individual trait, but rather a social construction-the product of cultural, political, and economic practices. This understanding does not deny biological and psychological differences, but emphasizes such differences gain meaning, often with severe neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 26 publications
0
44
0
4
Order By: Relevance
“…Second, selecting a school for parents of SWDs may be not as much about as the qualities of such a school but prior poor experiences with and perceptions of other schools of special education services. Waitoller and Super (2017) found that parents were unsatisfied with the special education services provided in traditional schools. Parents mentioned that the school in which they were placed through the IEP team 5 process did not have the services that their children needed (e.g., speech pathologist, occupational therapist, school counselor).…”
Section: Where Are Swds Within School Choice Research?mentioning
confidence: 99%
See 2 more Smart Citations
“…Second, selecting a school for parents of SWDs may be not as much about as the qualities of such a school but prior poor experiences with and perceptions of other schools of special education services. Waitoller and Super (2017) found that parents were unsatisfied with the special education services provided in traditional schools. Parents mentioned that the school in which they were placed through the IEP team 5 process did not have the services that their children needed (e.g., speech pathologist, occupational therapist, school counselor).…”
Section: Where Are Swds Within School Choice Research?mentioning
confidence: 99%
“…Even in districts that have high rates of inclusion, Black and Latinx students from low-income families are less likely than their White peers to be included in the general education classroom (LeRoy & Kulik, 2004). In this context, parents perceived schools of choice such as charter schools as being more inclusive due to their low student:teacher ratios, their lack of separated classrooms for SWDs, and what parents saw as a more motivated and young staff (Waitoller & Super, 2017).…”
Section: Where Are Swds Within School Choice Research?mentioning
confidence: 99%
See 1 more Smart Citation
“…These disabilities are attributed by the subjective judgements of school personnel, rather than by health professionals, and carry a greater educational stigma while attracting far fewer resources, relative to conditions like autism, which primarily affect whiter and wealthier young people. A major factor in this support gap is the role of parent initiative in acquiring and monitoring special education services (Trainor ; Waitoller & Super ; Clark ).…”
Section: Better Than Nothing?mentioning
confidence: 99%
“…This includes education policy scholarship that has explored and illuminated the importance of spatial discourses and perceptions of place in school reforms, school closures, parental choices, and youths' experiences of school choice (André-Bechely, 2007;Bell, 2009;Gulson, 2006;Lipman, 2011;Reay, 2007;Yoon, 2015). Alongside this is work that has drawn on critical race theory to show how policy and race are inexorably connected (for overviews in education and geography, see Gulson, 2010;Price, 2010) and the work of disability scholars in education that has connected the physical organization of school spaces to the politics of disability (Armstrong, 2003;Waitoller & Super, 2017). Influenced by the geographic canons of Lefebvre, Massey, and Soja, a range of qualitative research, without any use of GIS, has shed light on how people perceive, experience, and co-construct places where education policies unfold.…”
mentioning
confidence: 99%